Prevalence of Internet addiction and its associated factors among female students at Jouf University, Saudi Arabia - Doaa M. Abdel-Salam; Hajar I. Alrowaili; Haifa K. Albedaiwi; Amnah I. Alessa; Hanan A. Alfayyadh (SpringerOpen, 2019)
Abstract Background and objectives Internet addiction is an increasing problem among university students worldwide. The Internet provides numerous educational advantages, but too much Internet use can lead to unfavorable outcomes such as social isolation and poor academic achievement. The objectives of the present study were to assess the prevalence of Internet addiction and its associated factors among female students at Jouf University, Saudi Arabia. Methods A cross-sectional study using a multistage proportionate sampling technique was done. A self-administered questionnaire was distributed to the female students of Jouf University during face-to-face interviews with them. This questionnaire consisted of two parts; the first is a structured one for identifying sociodemographic features, and the second is Young's Internet Addiction Test (YIAT) to assess Internet use among the students. Results According to the YIAT scale of Internet addiction, 48.6% of the students were scored to be average Internet users. However, 49.5% and 1.9% of the students had moderate and severe addictions, respectively. The vast majority of students (94.6%) preferred home to access the Internet. Communication was the main purpose of using the Internet as it was reported by 47.3% of the students. The majority of the students (79.5%) utilized mobile phones for Internet access while other devices such as a laptop, tablets and desktop were used by 15.4%, 4.3%, and 3.2% of the students, respectively. More than half of the students (54.6%) used the Internet for an average of more than 4 h every day. Also, more than half (51.4%) used it in the evening being the dominant time of using the Internet. Internet addiction was significantly higher among students with high father education, students who sleep 6 h or less, students who utilize the Internet for entertainment purposes, and students who utilize the Internet mainly in the midnight. Conclusion Nearly half of female students at Jouf University have moderate or severe Internet addiction. The significant predictors of Internet addiction were sleeping hours ≤ 6, midnight as the dominant time for utilizing the Internet and using the Internet for entertainment purposes.